Społeczne aspekty problemu rozwodów - Rosset, Edward (Wydział Prawa i Administracji UAM, 1981)
At the very beginning the author declares himself against divorces. He does not mind legal institution of divorce, which is considered as indispensable, but disorganization of family life that leads to a divorce. Among the sources of growing phenomenon of family disintegration in contemporary world rash decisions of family setting up and the lack of responsibility for a family are mentioned. The author discusses divorces effects too, and among them: permanently growing number of „orphans after divorce" (they are children of disintegrated families), significant juvenile deliquency, misfortunes of abandoned women (half of the whole number of divorced women is doomed to lonely rest of life and to death in solitude). The author takes up also negative influence of family disintegration on fertility. According to the author, the growing number of divorces should act as an alarm signal. A struggle is necessary against harm, by which moral principles of society's life are impaired.
Social Aspects of the Divorce Problem